A calamity of souls - Baldacci, David (Grand Central Publishing, 2024)
"Set in the tumultuous year of 1968 in southern Virginia, a racially-charged murder case sets a duo of white and Black lawyers against a deeply unfair system as they work to defend their wrongfully-accused Black defendants. When two wealthy white landowners are found dead, the whole country immediately thinks it must be Jerome Washington, the hired help, who killed them. He was standing over the bodies when the police responded to an anonymous call and the only one on the property at the time of death. As far as the state is concerned, it's an open and shut case. Jack Lee, born and raised in Freeman County, knows that every man deserves a solid defense and agrees to be Jerome's lawyer, against everyone's better judgement. But as the facts of the case unfold, it becomes more and more obvious to Jack that this trial isn't about uncovering the truth and is instead a racially charged set up. And the whole town is calling for Jerome to receive the death penalty. Jack is soon ensnared in a system that's doing everything it can to prevent him from saving Jerome's life, and even he thinks all is lost. Then Desiree DuBose, a lawyer from up North with a social justice agenda, comes to town and quickly joins as co-council, blasting the case all over the news to gain support. But the citizens of Freeman County don't want to wait for the final verdict and Jack and Desiree find themselves in the crosshairs. Jack will need to stop at nothing to prove that Jerome is innocent even at the risk of his own life... and his family's"--